2019
DOI: 10.1007/s00170-019-04417-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Laser Powder Bed Fusion Benchmarking—Initial Trials with Inconel 625

Abstract: Production rate is an increasingly important factor in the deployment of metal additive manufacturing (AM) throughout industry. To address the perceived low production rate of metal AM systems based on single-laser powder bed fusion (L-PBF), several companies now offer systems in which melting has been parallelised by the introduction of multiple, independently controlled laser beams. Nevertheless, a full set of studies is yet to be conducted to benchmark the efficiency of multi-laser systems and, at the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Above 1000 • C, the δ phase was dissolved in the Ni matrix, so the hardness decreased rapidly. Wong et al [61] printed IN625 alloy using the multi-laser method and found that the average hardness (284.25 HV 0.5 ) and grain size (10-100 µm) of the samples obtained were the same as those reported in the literature (280 HV 0.5 [73]) by a single laser. They also found that heat treatment could reduce the hardness (271.08 HV 0.5 ).…”
Section: Hardness Distributionmentioning
confidence: 56%
See 4 more Smart Citations
“…Above 1000 • C, the δ phase was dissolved in the Ni matrix, so the hardness decreased rapidly. Wong et al [61] printed IN625 alloy using the multi-laser method and found that the average hardness (284.25 HV 0.5 ) and grain size (10-100 µm) of the samples obtained were the same as those reported in the literature (280 HV 0.5 [73]) by a single laser. They also found that heat treatment could reduce the hardness (271.08 HV 0.5 ).…”
Section: Hardness Distributionmentioning
confidence: 56%
“…The macroscopic characteristics of the as-built IN625 samples are closely related to the process parameters. It is obvious that the chevron feature of the track can be seen in almost all previous studies [55][56][57][58][59][60][61][62].…”
Section: (C)mentioning
confidence: 88%
See 3 more Smart Citations